Factors influencing occupational accidents: a multidimensional analysis in the electricity sector - Adriana Maria Silva Alves; Cid Gonçalves Filho; Nathália de Melo Santos; Gustavo Quiroga Souki (Gestão & Produção)
Abstract: Occupational accidents are a public health problem; therefore, it is necessary to conduct research that contributes to accident prevention and health promotion. To this end, this study aimed to investigate the main factors influencing work accidents at an electric power company. A survey of 1,027 in-house and outsourced employees of a large electric utility was conducted. The participants included injured and non-injured professionals. Organizational, personal/behavioral, and work/task factors were found to have statistically significant effects on work accident occurrence. As an academic and managerial contribution, the identification of the main factors that influence work accidents in the electric sector favors the development of strategies and actions for its control and mitigation.